Proteomic analysis of aquatic microbial responses to nanoparticulate and ionic silver - Barros, Diana Cláudia Martins Costa (2016)
Environmental biomarkers are the most promising next generation risk assessment tools, augmenting measurements of direct and highly sensitive responses at the cellular and sub-cellular levels. Silver nanoparticles (AgNPs) are among the mostly used nanoparticles and likely to be released in significant amounts to aquatic environments. Due to their antimicrobial properties, it is relevant to examine whether AgNPs can pose a risk to aquatic microbes in natural ecosystems. We used a bacterial strain, Pseudomonas sp. M1 (PsM1), isolated from sediments in a metal-polluted stream, to gain insights into the molecular mechanisms underlying its ability to deal with the toxic effects of AgNPs using a proteomic approach. We identified changes in the protein expression at AgNP concentrations inhibiting biomass production in 20% (EC20). After SDS-PAGE, the LC-MS/MS identified almost 200 proteins, about 50% of which increased its abundance under stress induced by AgNPs and Ag. Silver is known to react with proteins by combining with the thiol groups of enzymes, leading to protein inactivation. After AgNPs exposure, some of the upregulated proteins were associated with the degradation of transiently denatured and unfolded proteins, accumulated in the periplasm under stress conditions (e.g. periplasmic serine endoprotease). Exposure to AgNPs also induced proteins related to stress response, in particular, antioxidant enzymes, such as catalase-peroxidase and superoxide dismutase. The antioxidant response was consistent with our previous work suggesting that the ability to initiate an efficient antioxidant response is essential for the bacterium to cope with AgNP toxicity. We also found an increase in the proteins involved in amino acid (e.g. ornithine carbamoyltransferase) and energy metabolism (e.g. fructose-bisphosphate aldolase), which may reveal an AgNP-induced reorganization of the metabolic fluxes, that is compatible with an increased need of the bacterial cells to generate energy to support the defense mechanisms against AgNPs toxicity. An increased amount of chaperones (e.g. chaperone protein ClpB) was also found. These proteins play an essential role in the cell by assisting the correct folding of nascent and stress accumulated misfolded proteins and preventing their aggregation. AgNPs can likewise interact with elements of bacterial membranes, causing structural changes, dissipation of the proton motive + force, which is consistent with the increase in a specific porin with serine protease activity. Overall, PsM1’s response to the stress induced by AgNPs involved, among others, stress response proteins, proteins of the energy metabolism and transport proteins. Since the risk of the appearance of bacterial strains with augmented silver resistance is growing, it is highly recommended that the knowledge obtained from PsM1’s response to AgNPs be considered in future studies.